Routine activities and delinquency: the significance of bonds to society and peer context - Crawford, Lizabeth A. (Crime & delinquency, 2018)
This article extends prior research on routine activities and youth deviance by focusing on a broader range of routine activity patterns (RAPs) and on how their effects are conditioned by bonds to society and peer context. As hypothesized, the RAPs with the most consistent effects on delinquency were those lowest, or highest, in both structure and visibility. However, the relationship between school-related activities and delinquency was complex and varied across levels of the moderators in unexpected ways, given the structure and visibility of this RAP. Other RAPs, including unstructured peer interaction, affected delinquency independent of adolescents’ social relations, suggesting that neither social bonding nor external social control, via peer group norms, shapes the effects of situationally based opportunities for deviance on adolescents’ behaviors in a consistent manner.